2016
DOI: 10.1080/02699206.2016.1188421
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pausing in normal, fast and cluttered speech

Abstract: One of the main symptoms of cluttering is atypical pausing. However, there is little information about what this atypical pausing means, because typical speakers also have pauses not only at syntactic boundaries, but also within syntactic structures, and even within words. The aim of this study is to analyse how pausing strategies of persons who clutter differ from pausing strategies of normal speakers and speakers with exceptionally rapid speech (ERSs). Results show that there is a difference between the grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Other than PWC, there are also persons who produce similarly fast speech, but do not produce more disfluencies than typical speakers: they are persons who exhibit exceptionally rapid speech (ERS) (Bakker et al, 2011;Bóna, 2016). Bakker et al (2011, p. 47) define ERS as speech occurring faster than normal, but which does not show 'specific clinically significant characteristics of speech fluency'.…”
Section: Introductionmentioning
confidence: 99%
“…Other than PWC, there are also persons who produce similarly fast speech, but do not produce more disfluencies than typical speakers: they are persons who exhibit exceptionally rapid speech (ERS) (Bakker et al, 2011;Bóna, 2016). Bakker et al (2011, p. 47) define ERS as speech occurring faster than normal, but which does not show 'specific clinically significant characteristics of speech fluency'.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Garnett and St. Louis (2010) also reported twice as many disfluencies in PWC's speech than in the speech of typical speakers. Several studies, however, found no significant differences between PWC and typical speakers in the frequency of all disfluencies (Bakker et al, 2011;Myers et al, 2012;Bóna, 2016Bóna, , 2018. Contradictory results might emerge due to the small number of participants and large individual characteristics.…”
Section: Introductionmentioning
confidence: 92%
“…Further, Garnett and St. Louis (2010) also reported twice as many disfluencies in PWC's speech than in the speech of typical speakers. Several studies, however, found no significant differences between PWC and typical speakers in the frequency of all disfluencies (Bakker et al, 2011;Myers et al, 2012;Bóna, 2016. Contradictory results might emerge due to the small number of participants and large individual characteristics.…”
Section: Introductionmentioning
confidence: 92%